Quality Islamic Boarding School Model: Linking the Principles of Teacher Professionalism and Organizational Management - Syarifah Rahmah; Muhammad Anggung Manumanoso Prasetyo (Al-Hayat Al-Istiqomah Foundation collab with Letiges, 2022)
Contradictory professional and managerial principles such as quality monitoring and evaluation are integrated to shape contemporary professional action. This study aims to determine the directions of teacher professionalism and organizational management as a quality control model in Islamic boarding schools/dayah in Southeast Aceh district. This type of qualitative research with descriptive survey techniques. Primary data sources were obtained from informants and survey results, while preliminary data was obtained from various expert studies in the form of journals, books and other encyclopedias as support. Data analysis using an interactive model. The research data was then transcribed, and a data reduction process was carried out, which consisted of coding, choosing keywords, and categorization. The research results provide a model of professionalism as an aspect of change and 'organizing professionalism' as a new model. The Islamic boarding school teacher professionalism model leads to three parts: The formation of (1) Satisfaction Value of Quality Commitment; (2) Moral Commitment Trust Value, and (3) Performance Value for Continuous Change. The social implications expected through this research are a model of building organizational values in shaping teacher professionalism as an evaluative means of sustainable quality.